Biennale de l'Image en Mouvement 2018 the sound of screens imploding - Bellini, Andrea 1971-; Lissoni, Andrea 1970- (Maurizio Corraini, 2019)
Les artistes suivants ont participé à cet évènement : Lawrence Abu Hamdan, Andres Angelidakis, Korakrit Arunanondchai et Alex Gvojic, Meriem Bennani, Ian Cheng, Tamara Henderson, Kahlil Joseph, Fatima Al Qadiri & Khalid al Gharaballi, Sarah Abu Abdallah, Neil Beloufa, Irene Dionisio, James N. Kienitz Wilkins, Tobias Madison, Florent Meng, Bahar Noorizadeh, James Richards & Leslie Thornton, Eduardo Williams with Mariano Blatt, Elysia Crampton, Pan Daijing, Ligia Lewis
Impressum: Centre d'Art Contemporain Genève, 08.11.2018-03.02.2019; OGR - Officine Grandi Riparazioni Toino/Turin, 21.06-29.09.2019
Keywords: Geschichte 2016-2018; Performance -- Künste; Videokunst; Kunst; Ausstellungskatalog -- 08.11.2018-03.02.2019 -- Genf; Ausstellungskatalog -- 21.06.2019-29.09.2019 -- Turin; Bildband